Female Homicide Victimization in Spain from 1910 to 2014: the Price of Equality? - Linde, Antonia (European journal on criminal policy and research, 2021)
This paper studies trends in female homicide victimization in Spain from 1910 to 2014 and puts them in relation with several indicators of the evolution of women’s roles and status in the society. According to mortality statistics, female homicide victimization followed an overall upward trend interrupted only during the periods in which the country lived under dictatorships. Measures of women’s roles and status in society show a change from traditional to non-traditional roles since the 1960s. A multivariate autoregression analysis suggests that the female homicide victimization trend is correlated mainly with opportunity-based and non-gender sensitive variables.